Synthesis of hydroxy-functionalized star-branched PMMA by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Baskaran, Durairaj (Polymer Bulletin, 2009)
Living anionic polymerization has been exploited to synthesize hydroxy end-functionalized PMMA star-branched polymers. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been used to cross-link ethylene glycol dimethacrylate (EGDMA) in order to form star-branched polymers with cross-linked EGDMA core via `arm-first' method. The linear arms and the star molecules have been characterized by (1)HNMR, GPC, and light scattering. Variation in the number of arms with arm molecular weight and cross-linker loading has been studied. Star-branched PMMA-OH with as many as similar to 10 arms could be successfully made. Increased molecular weight of PMMA-OH led to decrease in the number of arms incorporated due to increased steric hindrance on the core. Increase in EGDMA concentration slightly increased the arm incorporation.
Keywords: Anionic polymerization; Star polymers; Star-branched PMMA